Spatial and temporal stability of mtDNA haplogroup frequencies in native North America - O'Rourke, Dennis H.; Hayes, M. G.; Carlyle, S. W. (Wayne State University Press, 2000)
Journal Article Mitochondrial DNA lineage frequencies in prehistoric Aleut, eastern Utah Fremont, Southwestern Anasazi, Pyramid Lake, and Stillwater Marsh skeletal samples from northwest Nevada and the Oneota of western Illinois are compared with those in 41 contemporary aboriginal populations of North America. The ancient samples range in age from 300 years to over 6,000 years.